PENGARUH PENDIDIKAN DAN PELATIHAN, PENGALAMAN KERJA DAN DISIPLIN KERJATERHADAP KINERJA PENGELOLA KEUANGAN DI UNIVERSITAS HALU OLEO - Saleh, Sri Wahyuni; Wawo, Andi Basru; Husin, Husin (Pascasarjana Universitas Halu Oleo, 2019)
This study aims to find out and analyze the Effect of Education and Training, Work Experience and Work Discipline on Financial Management Performance at Halu Oleo University. Respondents in this study were all employees who served as financial managers at Halu Oleo University. The total respondents were 106 people. Data analysis used in this study is multiple linear regression analysis techniques that are processed through SPSS version 23.0 for Windows software.The results of this study indicate that education and training have t (t-sig) of 0,000 which means that education and training have a positive and significant effect on the performance of financial managers, work experience has t (t-sig) of 0.118 which means that work experience has no effect and is not significant on performance financial managers, work discipline has t (t-sig) of 0.031 which means that work discipline has a positive and significant effect on the performance of financial managers. The conclusions in this study are education and training, work experience and work discipline simultaneously have a significant effect on the performance of financial managers. Education and training have a significant effect on the performance of financial managers, work experience has no effect and is not significant on the performance of financial managers and work discipline has a significant effect on the performance of financial managers in